The Investment Handbook : the Essential Funding Guide for Entrepreneurs. - Bateman, David (London : Legend Business Books, 2019)
The all you need to know guide to Investment. The yearbook is packed with practical guidance on who to contact and how to get investment.
Cover; Title; Copyright; Contents; Foreword; Introduction; Part One -- Preparing to Approach and Meet Investors; 1.1 What Investors Want in Return; 1.2 Common Mistakes -- an Investor's View; 1.3 Valuing Your Business; Part Two -- Directory of Investors; 2.1 How to Use the Directory; 2.2 UK Venture Capital Investors; 2.3 UK Angel Networks; 2.4 US Venture Capital Investors; 2.5 US Angel Networks; 2.6 Rest of World Capital Investors; 2.7 Rest of World Angel Networks; Part Three -- Down the Road; 3.1 What to Do When You Don't Get Funding; 3.2 Endgame; Conclusion
Print version record.
Master record variable field(s) change: 050, 082
Keywords: Business enterprises -- Finance; Business planning; Electronic books